Experimental modal identification of an existent earthen residential building - Aguilar, Rafael (2013)
The paper presents the preliminary round of in-situ experimental tests carried out at “Hotel Comercio”, a historical construction located at the historical centre of Lima (capital of Peru). The building is a three story republican-type construction built at 19th Century with composite structure of Adobe and “Quincha”. The experimental works consisted on Operational Modal Analysis (OMA) tests aiming at identifying the dynamic characteristics of the building using the environmental noise as source of excitation. The severe damage at the Hotel, as well as its complex boundary conditions made the dynamic identification process hard to carry out. The experimental results showed coupled global and local modes. The expected different behaviour of the Quincha panels and the Adobe in terms of flexibility was also verified. The Finite element model of the building was implemented and a preliminary numerical model updating was carried out. The modal comparison of the numerical and experimental results evidenced that few modes were accurately assessed by the analytical approach. An important contribution of the paper is the introduction of OMA as a tool for better understanding the structural behaviour which may also allow assessing the real damage condition of the buildings.